The application of Material Flow Cost Accounting for loss reduction in the pottery and decorative ceramics production process - Rungchat Chompu-Inwai (2018)
© 2015 IEEE. The case study company, which is located in northern Thailand, manufactures pottery and decorative ceramics. During a preliminary study, it was found that defects and losses occurred within several of the company's production processes. The aim of this research study was to analyze, classify and identify the losses incurred in terms of costs during the case study company's production process, using the Material Flow Cost Accounting Technique (MFCA). Based on the analysis of materials flows and energy usage, MFCA can help a company improve both its financial and environmental performance. MFCA focuses on both the product costs and the materials loss costs. The ultimate purpose of this research was to identify opportunities for reducing materials usage and losses, improve the efficiency of materials and energy usage, and reduce adverse environmental impacts. After the MFCA analysis had been carried out, methods that could be applied to reduce losses and improve the production process were developed.